LEGAL PROBLEMS OF REGULATING AGRICULTURALCOOPERATION IN THE REPUBLIC OF KAZAKHSTAN (INTERNATIONAL SCIENCE REVIEWS. SOCIAL SCIENCES SERIES, 2024)
This paper considers the main theoretical and practical issues of the legal regulation of an agricultural cooperative in Kazakhstan. First, agriculture is one of the main sectors of the economy of the Republic of Kazakhstan. The research of the legal problems of agricultural cooperation affects the solution of food security problems. The authors focuses on the relevance of the studied problem, determined the place and role of agricultural cooperation, gives its definition by comparing different points of view of scientists, conducts a comparative analysis of the legislation of foreign countries in the studied area, identifies problems in the legislation and suggests ways to improve existing legislation in this area.Furthermore, the authors suggests legislatively consolidating the system of principles of agricultural cooperation.